The Effectiveness of Accelerating Stunting Reduction Policy - Sevilla, Jenifer; Nugroho, Asianto; Turymshayeva, Arida (Lembaga Contrarius Indonesia, 2024)
Indonesia has implemented various policies to accelerate stunting reduction, however whether these policies have effectively reduced stunting, because the prevalence of stunting is still high, at 30.8%. The government's involvement in creating and implementing stunting policies in Indonesia still needs to be effective in terms of legal substance, structure, and culture. This research employs socio-legal research methods and a comparative approach with Finland. This research shows, first, that the existing acceleration policy has yet to effectively overcome the problem of stunting in Indonesia because there is still a policy of implementing taxes on nutritious food commodities, which affects people's purchasing power. There is a need for socialization and integration of stunting policies across sectors, technical coordination between central and regional government organizations, and community participation in policy implementation. Second, comparative studies in Finland can provide new information regarding understanding health and formulating regulations for implementing taxes on unhealthy foods. Therefore, this research has the potential to enhance the prevention of stunting and provide valuable insights for the Indonesian government to formulate and implement policies.